Diversity of agroforestry practices in Viet Nam - Mulia, R.; Nguyen, M.P. (World Agroforestry Centre, 2021)
Agroforestry is one of traditional farming practices in Viet Nam. It varies in forms, plant components and species to fit into diverse topographical and climatic conditions as well as preferences of local people across the country. In the past decades, driven particularly by expansion of intensive monocropping practices, the area of agroforestry in the country has been shrinking. However, rural people still maintain agroforestry for different purposes, including as subsistence and income-generating farming system in home gardens, as part of their livelihood strategies. To respond to global challenge of food insecurity and climate change, research and development communities worldwide have put significant attention to agroforestry as potential solution to reconcile economic and ecological pressure, and to achieve sustainable development. Furthermore, the recent Covid-19 pandemic has called a strong need to strengthen local food systems, to include farming systems around homestead that can provide diverse products for different purposes. An increasing awareness on benefits that can be derived from agroforestry also takes place in Viet Nam, and recently, the country has included agroforestry in its 2020 Nationally Determined Contributions as a measure for land conservation to maintain food production, and for carbon sequestration to combat climate change. This book describes a high diversity of agroforestry practices in Viet Nam and can help (re-)introduce and support wider development of agroforestry in the country. ICRAF Viet Nam team has conducted a literature review and compiled information on agroforestry practices from different ICRAF projects and studies in Viet Nam. The book provides key information of all agroforestry practices presented, including plant components, distribution across the country, and actual or potential benefits. It also provides relevant photos for most of the systems to better illustrate them.